Heterogeneous Influence of Glacier Morphology on the Mass Balance Variability in High Mountain Asia. Issue 6 (3rd June 2019) - Brun, F.; Wagnon, P.; Berthier, E.; Jomelli, V.; Maharjan, S. B.; Shrestha, F.; Kraaijenbrink, P. D. A.
Abstract : We investigate the control of the morphological variables on the 2000–2016 glacier‐wide mass balances of 6, 470 individual glaciers of High Mountain Asia. We separate the data set into 12 regions assumed to be climatically homogeneous. We find that the slope of the glacier tongue, mean glacier elevation, percentage of supraglacial debris cover, and avalanche contributing area all together explain a maximum of 48% and a minimum of 8% of the glacier‐wide mass balance variability, within a given region. The best predictors of the glacier‐wide mass balance are the slope of the glacier tongue and the mean glacier elevation for most regions, with the notable exception of the inner Tibetan Plateau. Glacier‐wide mass balances do not differ significantly between debris‐free and debris‐covered glaciers in 7 of the 12 regions analyzed. Lake‐terminating glaciers have more negative mass balances than the regional averages, the influence of lakes being stronger on small glaciers than on large glaciers. Key Points: Debris‐free and debris‐covered glaciers have statistically indistinguishable glacier‐wide mass balances over 2000–2016 Lake‐terminating glaciers on average have more negative mass balances than land‐terminating glaciers Morphological variables explain 8% to 48% of the variance of High Mountain Asia glacier mass balances for the period 2000–2016